Analisis Model Group Investigation Mengembangkan Berpikir Kritis Siswa Era Globalisasi pada PKn - Adnin, Ismi; Sapriya, Sapriya; Komalasari, Kokom; Islam, Kireida Rona; Mubarok, Muhammad Fajri (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The era of globalization requires every individual to be able to think critically in order to face challenges. This can be done by developing students' critical thinking skills through the use of appropriate learning models, namely the Group Investigation (GI) type model which supports this achievement, of course in line with the desired core Civics learning . This research is qualitative research using the literature review method. The research results show that the use of the GI model in developing students' critical thinking in Civics lessons does act as a guide for students in the current era of globalization to make a contribution to themselves, others, and even the nation.